Hubungan antara Lingkungan Fisik dengan Kelelahan Kerja Pegawai Produksi di Pabrik Tahu Sutera Galih Dabeda - Gurdani Yogisutanti; Dhony Firmansyah; Suyono Suyono (Universitas Ahmad Dahlan, 2020)
Background: Fatigue is a workplace accident that decreased efficiency and endurance at work. This study aims to determine the factors that influence work fatigue in tofu production workers at the Galih Dabeda Silk Tofu Factory Kampung Cibuntu Bandung. Method: The research was cross sectional design and sample in the form of total sampling with a total of 80 employees. Data collection is done through interviews and direct measurements. Data analysis was performed univariately and bivariately with chi square test and the magnitude of the relationship (OR). Results: Factors related to work fatigue are noise (p-value 0,0001) and lighting (p-value 0,0001), but heat stress (p-value 0.532; OR 1.045 95%; 0.987- 1,112) did not correlate with fatigue. Conclusion: The conclusion that can be drawn from this study is the noise and lighting associated with the occurrence of work fatigue in employees in the factory know, while the heat pressure is not proven to be associated with work fatigue. Suggestions that can be recommended are to provide alternating hours of rest for 30-60 minutes to employees, use personal protective equipment as needed and drink water at least 8-10 glasses a day or 160 - 200 ml of water in one day according to their respective needs the worker.